ANALISIS PENYUSUNAN ANGGARAN PENJUALAN PADA PT. INDOFOOD TBK. - Siti Andriyani; Siti Nur Aisyah; Bella Sumberliana; Rachmat Agus Susanto (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2023)
A company's sales budget is a tool to measure the size of the budget that the company has set from year to year. This research aims to determine the effectiveness of the budget set by the company using the top down method and recommend companies use the right method with appropriate budget estimates. The research object is PT. Indofood Tbk which operates in the processed food sector. This research uses quantitative descriptive analysis methods. The type of data used by the author in this research is primary data in the form of financial reports and secondary data in the form of processed food sales data per year. The data collection technique used in this research is observation. The research results show that PT. Indofood still uses the top down method in determining its sales budget from year to year and will try to use the sales budget estimation method for the future. The analysis of sales budget preparation that the author uses in analyzing the budget is using the straight line trend analysis method because using this method does not produce too many differences.